2021
DOI: 10.1111/jace.18077
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between Ln leaching and Ln–O binding energy in monazite (Nd, Sm, Eu)

Abstract: There are a large number of αemitters with long-life in nuclear materials inventories and nuclear waste around the world, including Pu and minor actinides (Np, Am, and Cm). 1,2 These long-lived actinides are suggested to be separated than being immobilized in mineral-based ceramics to prevent the migration of radionuclide in the biosphere. 3 Monazite has been proposed as the potential actinides host-matrices owing to its excellent long-term stability. 4-6 An 3+ PO 4 monazite waste forms can be easily obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The long‐term chemical stability of monazite benefits from the protection of rhabdophane (LnPO 4 ⋅0.667H 2 O) precipitation on the surface of the specimen 22,23 . It is generally believed that the leaching actinides from monazite matrix will be adsorbed immediately by the defective area of monazite surface to the nucleation of Ln x An 1‐ x PO 4 ·0.667H 2 O rhabdophane precipitation 16,24,25 . Recently, Gausse et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long‐term chemical stability of monazite benefits from the protection of rhabdophane (LnPO 4 ⋅0.667H 2 O) precipitation on the surface of the specimen 22,23 . It is generally believed that the leaching actinides from monazite matrix will be adsorbed immediately by the defective area of monazite surface to the nucleation of Ln x An 1‐ x PO 4 ·0.667H 2 O rhabdophane precipitation 16,24,25 . Recently, Gausse et al.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 It is generally believed that the leaching actinides from monazite matrix will be adsorbed immediately by the defective area of monazite surface to the nucleation of Ln x An 1-x PO 4 ⋅0.667H 2 O rhabdophane precipitation. 16,24,25 Recently, Gausse et al reported that the standard solubility products (log Ksp) of LnPO 4 ⋅0.667H 2 O rhabdophane in 0.1 mol/L HCl solutions at 298-343 K are approximate 25, implying the feasibility of separation-enrichment of actinides from rhabdophane in acidic solutions. 26 Nano-sized plutonium iron phosphate hydroxide structurally related to the rhabdophane group minerals was found in Hanford site sediments including Pu waste in the 216-Z9 crib sediment in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution experiments of La 0.666 Nd 0.167 Sm 0.167 PO 4 monazite ceramics were performed at 363 K in pH = 5, 7, and 9 solutions to assess the chemical stability of ceramics in geological environment and to gain a general understanding of lanthanides leaching activity. Previous studies reveal that the weak leaching resistance of monazite ceramics has been found in different leachates at initial 7 days owing to surface defect caused by mechanical polishing, 32 and that the stable state corresponding to dissolution–diffusion phenomenon has been established after 21 days with an LR value of ∼10 −6 –10 −5 g/m 2 in pH = 5 solution 35 . It should be noted that the updated leachates in previous studies were not digested with strong acid prior to ion concentration measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies reveal understanding the corrosion mechanism of monazite requires a fundamental knowledge of Ln–O bond properties and lanthanides vacancy defect chemistry in monazite surface 21,32 . To deeply investigate the leaching activity of La 0.666 Nd 0.167 Sm 0.167 PO 4 monazite, the formation energies of lanthanides (Ef${E_f}$) with and without charge state q are analyzed by the following equations 33 : EfXq=EtotXqEtotB+iniμi+qεf+EVBM+Ecorr$$\begin{eqnarray} {E_f}\left( {{X^q}} \right) &=& \;{E_{tot}}\left( {{X^q}} \right) - {E_{tot}}\left( B \right)\nonumber\\ && + \mathop \sum \limits_i {n_i}{\mu _i} + q\left( {{\varepsilon _f} + {E_{VBM}}} \right) + {E_{corr}}\end{eqnarray}$$where Etot(Xq)${E_{tot}}( {{X^q}} )$ and Etot(B)${E_{tot}}( B )$ are the total energy of surface structure with and without vacancy defect ( X ).…”
Section: Experimental and Theory Calculationmentioning
confidence: 99%
See 1 more Smart Citation